The Restriction between the linguistic rankwith meaning and inflective guidance (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research deals with the relationship between the meaning and the linguistic rank. It starts talking about the idiom of the linguistic standing of a word in a sentence according to the ancient and modern scholars. It also includes the role of the linguistic standing in declaring the meaning and the relation of the linguistic sign in this concern. The linguistic rank is a part in a group called evidences, and it is two kinds: the fixed standingin which the words stand in a series that each one leads to the other. So the antecedent refers to the subsequent and the second word completes the meaning of the first one. And the flexible rank in which the word is characterized with flexibility of the linguistic standing which gives it semantic function or necessity of grammatical cause in exceeding the position. The research shows the relationship between the linguistic standing and the meaning where there is an intimate relation between them, and the whole context is the main base in the sentence order. To clarify this, the research analyses group of quotations. The research also shows the meaningful worth to change the final part the word and the intimate relation by showing the different meanings of the expression and the connection of this withsyntactic guidance and the linguistic rank and with return of the linguistic guidance to many reasons.